Visas as Preventive Legal Protection for the Sovereignty of the State of Indonesia: The Perspective of the Selective Policy Principle in Indonesian Immigration Law - Ni Putu Pera Krisna Dewi; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
A visa is understood as a specific permit to reside for foreign nationals. In Indonesia, Law No. 6/2011 on Immigration affirms the applicability of the Selective Policy principle to ensure that not everyone can easily stay in Indonesia, particularly with certain requirements to ensure national security and sovereignty. This research aims to analyze visas as an instrument of preventive legal protection for Indonesia's national sovereignty in relation to the implementation of the Selective Policy principle. This research is normative legal research with a conceptual and legislative approach. The research findings confirm that visas are a preventive legal protection effort for the sovereignty of the Indonesian state because they allow for the identification of the background of individuals seeking residency permits in Indonesia. As a preventive legal protection effort for state sovereignty, visas are relevant to the principle of Selective Policy in Indonesian immigration law, which emphasizes state sovereignty and security as the most important aspects, making the restriction of residency permits thru visas relevant.